Green Areas and Avian Species Richness in the University of Malaya Campus, Peninsular Malaysia - Ramli, R. (Faculty of Science, University of Malaya, 2004)
A survey was conducted within the University of Malaya campus in Peninsular Malaysia to determine the relationship between bird species richness and forest patches. Two standard procedures (direct observation and mist-netting) were used in the survey. A total of 87 species of birds was recorded in the study area. Although most of the species observed in this area are resident species and with no conservation implication, 22 species have been classified as globally threatened. The presence of these species indicates that the University of Malaya campus can play an important role in wildlife management and conservation particularly of urban birds.